The time management styles of deputy ministers in Canada: Towards a taxonomy. (12th August 2022) - Dutil, Patrice; Migone, Andrea
Abstract: Deputy Ministers in Canada play a critical role in defining all aspects of policy and operations for their respective departments and also contribute significantly to their government's collective initiatives. While there exists a solid understanding of the roles and functions of Deputy Ministers, there is little perception of how individuals actually shape the position in terms of time management. Understanding how senior executives in Canadian public service organize their time is critical to an appreciation of how they prioritize their functions. Using results from a 2020 survey, this study documents how Deputy Ministers in Canada divide their weeks in terms of personal work and meetings. This study goes further to discern a taxonomy of five time‐allocation styles of Deputy Ministers: Operational, Balanced, Managerial, Strategic and HR‐Focused. Sommaire: Au Canada, les sous‐ministres jouent un rôle crucial pour définir tous les aspects des politiques et des opérations de leurs ministères respectifs et contribuent aussi considérablement aux initiatives collectives de leur gouvernement. Bien que les rôles et les fonctions des sous‐ministres soient bien compris, l'on saisit très peu la manière dont les individus influencent réellement ce poste en termes de gestion du temps. Comprendre comment les cadres supérieurs de la fonction publique canadienne organisent leur temps est essentiel pour apprécier la façon dont ils priorisent leurs fonctions. À partir des résultats d'un sondage de 2020, cette étude documente comment les sous‐ministres au Canada organisent leurs semaines en termes de travail personnel et de réunions. Nous poussons l'étude plus loin pour percevoir une taxonomie de cinq styles de répartition du temps des tâches des sous‐ministres : opérationnel, équilibré, gestionnaire, stratégique et axé sur les ressources humaines.